RETRACTED ARTICLE: The Role of Cyclooxygenase-2, Interleukin-1β and Fibroblast Growth Factor-2 in the Activation of Matrix Metalloproteinase-1 in Sheared-Chondrocytes and Articular Cartilage - Pei-Pei Guan; Jing-Wen Guo; Xin Yu; Yue Wang; Tao Wang; Konstantinos Konstantopoulos; Zhan-You Wang; Pu Wang (Scientific Reports)
Abstract MMP-1 expression is detected in fluid shear stress (20 dyn/cm2)-activated and osteoarthritic human chondrocytes, however, the precise mechanisms underlying shear-induced MMP-1 synthesis remain unknown. Using primary chondrocytes and T/C-28a2 chondrocytic cells as model systems, we report that prolonged application of high fluid shear to human chondrocytes induced the synthesis of cyclooxygenase-2 (COX-2), interleukin-1β (IL-1β) and fibroblast growth factor-2 (FGF-2), which led to a marked increase in MMP-1 expression. IL-1β, COX-2-dependent PGE2 activated the PI3-K/AKT and p38 signaling pathways, which were in turn responsible for MMP-1 synthesis via NF-κB- and c-Jun-transactivating pathways. Prolonged shear stress exposure (>12 h) induced 15-Deoxy-Δ12,14-prostaglandin J2 (15d-PGJ2) synthesis. Although 15d-PGJ2 suppressed PI3-K/AKT and p38 signaling pathways, it stimulated MMP-1 expression via activating heme oxygenase 1 (HO-1). The critical role of COX-2 in regulating MMP-1 expression in articular cartilage in vivo was demonstrated using COX-2+/− transgenic mice in the absence or presence of rofecoxib oral administration. These findings provide novel insights for developing therapeutic strategies to combat OA.